KOMPOSISI DAN KEANEKARAGAMAN SERANGGA TANAH DI ARBORETUM UNIVERSITAS RIAU SEBAGAI SUMBER BELAJAR MELALUI MODEL INKUIRI - Suwondo ' '; Elya Febrita '; Andri Hendrizal ' (Biogenesis, 2015)
This research aims to determine the composition and diversity of soil insect in Riau University Arboretum, and obtains an alternative learning source. The method of this research is survey. Locations were selected based on purposive random sampling considering 3 habitat types. The parameters used in this study is the composition and diversity of soil insect. Physical and chemical parameters measured were soil temperature, pH, water content and organic matter content. The data obtained are presented in tables and graphs then analyzed descriptively to be associated with the learning set of material. Based on the research that has been conducted, there are differences in the composition of soil insects at each research station. Of the three stations, there were obtained 5 orders and 12 species. Order were found which is consist of Hymenoptera, Collembola, Orthoptera, Coleoptera and Diptera. At the first station, found as many as 494 individual. At the second station, there was found as many as 217 insects and found 271 insects in stations III. The diversity of soil insect is classified as moderate with scale 1-3. The results can be used to develop inquiry-based learning animal diversity in the form of Student Work Sheet.Keywords : Composition, Diversity, Learning Inquiry, Soil Insect